Correlation between the Rotation of the First Molars and the Severity of Class II Division 1 Malocclusion - Betânia Pessoa Lima; Célia Regina Maio Pinzan-Vercelino; Laércio Santos Dias; Fausto Silva Bramante; Rudys Rodolfo De Jesus Tavarez (The Scientific World Journal)
This study aimed to evaluate the potential correlation between the severity of Class II division 1 malocclusion and the magnitude of mesiopalatal rotation of the maxillary first molars. Scanned images of 104 cast models were grouped according to the severity of Class II malocclusion as follows: Group 1, 1/4 Class II malocclusion; Group 2, 1/2 Class II malocclusion; Group 3, 3/4 Class II malocclusion; and Group 4, complete Class II malocclusion. The rotation was measured using parameters described by Henry, Friel, and Ricketts, referred to as indicators 1, 2, and 3, respectively. The correlation was evaluated using the Spearman’s correlation coefficient. The rotational indicators were compared using one-way analysis of variance. For all statistical analyses used p<0.05, a positive correlation was observed between the severity of Class II malocclusion and the mesiopalatal rotation of the maxillary first molar. This correlation was statistically significant for indicator 1 between Groups 1 and 3 and for indicator 2 between Groups 1 and 4, which include cases of extreme malocclusion. In conclusion, there is a positive correlation between the severity of Class II division 1 malocclusion and the magnitude of mesiopalatal rotation in the maxillary first molars.